The fraternal economy : a pastoral psychology of Franciscan economics - Couturier, David B. (South Bend, Ind. : Cloverdale Books, 2007)
"The fraternal economy is presented as a new way of relating economically and socially, one that builds trust and communion rather than suspicion, exhaustion and division. This work brings together insights from two disciplines, pastoral psychology and organizational development, helping readers understand how they can live and work in a more just and collaborative way"--Provided by publisher.
The development of the fraternal economy -- Toward the psychodynamics of gospel -- Brotherhood : an introduction to the psychosocial theory of self-transcendent consistency -- The belief in a fraternal world : a fundamental delusion? -- The fraternal economy and the development of the corporate imagination : a socio-analytic perspective -- The development of communities of international compassion -- Towards a pastoral psychology of Franciscan economics.
Includes bibliographical references (p. 197-200) and index.
Keywords: Franciscans; Capuchins; Communities -- Religious aspects -- Christianity; Fraternal organizations; Pastoral psychology; Economics -- Religious aspects -- Christianity